Using recreational echo-sounders for marine science studies - Parnum, Iain; Ellement, T.; Perry, M.; Parsons, Miles; Tecchiato, Sira (2017)
In recent years, recreational echo-sounders, such as the Humminbird, Lowrance and Simrad Yachting brands, have become more advanced. These brands now offer models with the ability to log not just depth, but acoustic data from the different transducers. This paper presents methods for converting, processing and visualising data collected by recreational sounders. Examples of visualising fish aggregations and seafloor mapping are given. The examples show both the potential and the drawbacks of using such systems.